Retracted: Distributions of trace elements with long‐term grazing exclusion in a semi‐arid grassland of inner Mongolia - Juan Hu; Qiang Li; Yingxin Huang; Qilin Zhang; Daowei Zhou (Ecology and Evolution, 2022)
Abstract We still know little about the distributions of trace elements in grassland with long‐term grazing exclusion. The contents, stocks, and proportions of iron (Fe), aluminum (Al), manganese (Mn), and boron (B) in green plant–litter–root–soil were evaluated by enclosing for 18‐, and 39 years inside the fence (F18 and F39) and grazing outside the fence (F0) in Mongolia grassland. Results showed that F18 and F39 decreased the stocks of Fe, Al, and Mn in green plant and root compared with F0 (p < .05), while increased the stocks of them in litter (p < .05). The F18 obviously increased the stocks of Fe and Mn in soil, especially B (p < .05). The stock of Fe, Al, and Mn in green plant at F39 was 28.6%, 13.9%, and 39.2% higher than that at F18. The stocks of trace elements in undecomposed litter at F39 were increased by 12.7%–52.2% compared with F18, while the stocks of them in complete decomposed litter were decreased by 32.2%–42.5%. The stocks of trace elements in soil at F39 were 9.1%–28.0% lower than that at F18, especially B (p < .05). In conclusion, the trace elements were mainly shifted from green plant and root to soil and complete decomposed litter with 18‐year grazing exclusion. The trace elements were shifted from complete decomposed litter and soil to root with 39‐year grazing exclusion compared with 18‐year grazing exclusion.